An Exploratory Study of Organizational Culture in Philippine Firms - Racelis, Aliza D. (Philippine Management Review, 2010)
Organizational culture studies have proliferated in the management literature in recent years.  This is largely because the study of the culture concept prompts researchers to question commonly held assumptions about organizations and their value to society.  This study seeks to describe and characterize, at an exploratory level, the culture in Philippine organizations. Results of a questionnaire survey of 136 Philippine managers regarding their firms' organizational culture show that specific industries may share common cultural characteristics along the organic-mechanistic and integration-differentiation continuums, and that some of those commonalities might be explained by similarities in their competitive environment, customer requirements, and societal expectations.  These results, however, have yet to be verified by similar explorations into other demographic variables such as company size. This study can be extended by exploring the relationships between the resulting cultural variables and such organizational characteristics as: firm size, financial performance, stock price performance, ethical behavior, work satisfaction, corporate success factors, firms' market-orientedness, success in mergers and acquisitions, various other performance variables, etc.